Effective School Leaders in Nepal - Ghimire, Shurendra (BMC Journal of Scientific Research, 2022)
This paper contributes knowledge of the reasons behind a few public schools achieving good results in students’ learning and attracting many students despite almost all public schools suffering from falling education quality and student numbers. The cases of two schools-one from city-located affluent and another sub-urban poor schools were taken to conduct an ethnographic study and cross-validate the findings. The study suggests that the role of the chairperson is more dominant than the head teacher in selected schools. Visionary commitment, devotion, and repeated tenure of chairpersons of the school management committee are the source of school effectiveness, the gradual progress in education quality, and the incremental growth of students. Chairpersons’ performances are boost by their motivation of fulfilling their needs of ’social recognition’ and ’experimenting quality education’ through school leadership or bringing changes in school; they have already fully filled their physiological needs (Maslow, 1943). Meanwhile, these chairpersons are influenced by the socioeconomic ideology of ’quality education in public schools is the state’s accountability for promoting equality and access to the marginalized group’. It also suggests that chairmanship is a process than the traits, anyone can lead a school regardless of academic and work experience if guided by an ideology and motivated to fulfill higher level needs.